2018
DOI: 10.3892/ol.2018.8051
|View full text |Cite
|
Sign up to set email alerts
|

CD44 promotes cell proliferation in non-small cell lung cancer

Abstract: Cluster of differentiation 44 (CD44), a marker for cancer stem cells, has been reported to be associated with poor prognosis in non-small cell lung cancer (NSCLC), but its involvement in tumor growth has not fully been elucidated. The present study explored the associations between CD44 expression and clinicopathological features using immunohistochemistry in 94 NSCLC cases, as well as proliferation in cells with aberrant expression of this protein. Overexpression of CD44 was achieved by transfecting H1299 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 25 publications
4
35
0
Order By: Relevance
“…In agreement with our results, Hu et al reported that knockdown of CD44 expression inhibited cell proliferation and colony formation in non-small cell lung carcinoma. 26 Additionally, CD44 silencing could suppress triple-negative breast cancer cells’ growth and migration. 27 Similar observations have also been reported in bladder cancer, malignant pleural mesothelioma as well as head and neck squamous cell carcinoma, 28 30 strongly suggesting new research directions based on the potential of CD44 as a prognostic biomarker and therapeutic target in GBC.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our results, Hu et al reported that knockdown of CD44 expression inhibited cell proliferation and colony formation in non-small cell lung carcinoma. 26 Additionally, CD44 silencing could suppress triple-negative breast cancer cells’ growth and migration. 27 Similar observations have also been reported in bladder cancer, malignant pleural mesothelioma as well as head and neck squamous cell carcinoma, 28 30 strongly suggesting new research directions based on the potential of CD44 as a prognostic biomarker and therapeutic target in GBC.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that treatment of lung adenocarcinoma A549 cell with ATRA led to the downregulation of ALDH1A1 [34]. RA can reduce the ALDH activity and CD44 expression, thus affecting cell proliferation, cancer invasiveness and sensitivity to various chemotherapy drugs [24,35,36]. ALDH1A1 has been shown to convert/oxidize retinaldehyde into retinoic acid (RA) in several tissues, and to be one of the target proteins of ATRA [15].…”
Section: Discussionmentioning
confidence: 99%
“…The existence of CSC expressing CD44 and a high ALDH1A1 activity has been demonstrated in NSCLC [21][22][23]. The ALDH1A-RA signaling is involved in cancer cell proliferation, invasiveness and sensitivity to various chemotherapy drugs [24]. Retinoic acid potentiates the chemotherapeutic effect of cisplatin by inducing differentiation of CSC in several cancers [25], and adding all-trans retinoic acid (ATRA) to chemotherapy based on paclitaxel and cisplatin as first-line treatment could increase response rate (RR) and progression-free survival (PFS) in patients with advanced NSCLC [26].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CD44 is a transmembrane glycoprotein belonging to the adhesion molecule family and serves a role in numerous physiological and pathological processes. CD44 has been demonstrated to serve a significant role in tumor invasion, metastasis and drug resistance ( 35 ). Yan et al ( 36 ) and Bourguignon et al ( 37 ) have demonstrated that CD44 is closely associated with drug resistance exhibited by colon CSCs.…”
Section: Discussionmentioning
confidence: 99%